Multi-Valent Protein Hybrid Pneumococcal Vaccines: A Strategy for the Next Generation of Vaccines - Ninecia R. Scott; Beth Mann; Elaine I. Tuomanen; Carlos J. Orihuela (Vaccines, 2021)
Streptococcus pneumoniae (Spn) is a bacterial pathogen known to colonize the upper respiratory tract and cause serious opportunistic diseases such as pneumonia, bacteremia, sepsis and meningitis. As a consequence, millions of attributable deaths occur annually, especially among infants, the elderly and immunocompromised individuals. Although current vaccines, composed of purified pneumococcal polysaccharide in free form or conjugated to a protein carrier, are widely used and have been demonstrated to be effective in target groups, Spn has continued to colonize and cause life-threatening disease in susceptible populations. This lack of broad protection highlights the necessity of improving upon the current “gold standard” pneumococcal vaccines to increase protection both by decreasing colonization and reducing the incidence of sterile-site infections. Over the past century, most of the pneumococcal proteins that play an essential role in colonization and pathogenesis have been identified and characterized. Some of these proteins have the potential to serve as antigens in a multi-valent protein vaccine that confers capsule independent protection. This review seeks to summarize the benefits and limitations of the currently employed vaccine strategies, describes how leading candidate proteins contribute to pneumococcal disease development, and discusses the potential of these proteins as protective antigens—including as a hybrid construct.